2003
DOI: 10.1063/1.1574798
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the hydroxylated (0001) surface of α-Al2O3

Abstract: Self-consistent density functional calculations of the hydroxylated ͑0001͒ corundum surfaces are presented. It is demonstrated that the hydroxylated surfaces are the most stable under most, but not all, conditions. Hydroxylation significantly lowers the surface free energy of ␣-alumina. The stability of the hydrated surface resolves the discrepancies between the morphology of the ␣-alumina ͑0001͒ surface observed under ultra-high vacuum, and at ambient conditions. A method for the calculation of the equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 27 publications
14
168
0
1
Order By: Relevance
“…For example, Wang et al 15 showed that the single Al-terminated surface is stable up to high oxygen partial pressures with large inward relaxations, but that the O-terminated surface can be stabilized by hydrogen. Other calculations have confirmed that hydrogen strongly affects the surface, 3,[16][17][18] and different terminations of the clean and hydrated surface have also been observed experimentally. 19 Moreover, the dissociation mechanism of water on the surface has been thoroughly investigated, and H 2 O has been shown to dissociate readily.…”
Section: Introductionmentioning
confidence: 57%
“…For example, Wang et al 15 showed that the single Al-terminated surface is stable up to high oxygen partial pressures with large inward relaxations, but that the O-terminated surface can be stabilized by hydrogen. Other calculations have confirmed that hydrogen strongly affects the surface, 3,[16][17][18] and different terminations of the clean and hydrated surface have also been observed experimentally. 19 Moreover, the dissociation mechanism of water on the surface has been thoroughly investigated, and H 2 O has been shown to dissociate readily.…”
Section: Introductionmentioning
confidence: 57%
“…29 Moreover, no UV or similar spectroscopic studies have been reported for the clean or hydroxylated surface that may be related to surface F centers. Since the main interests of this work is to identify the role of the vacancy coordination and relaxation in the excitation energies only the simplest clean surface has been considered.…”
Section: Spectroscopic Features Of Surface Vacancy Centersmentioning
confidence: 99%
“…28 Nevertheless, it is worth pointing out that this surface is rather difficult to obtain experimentally due to its rapid hydroxylation. 29,30 The surface O-vacancy models have been obtained by removing a single O atom ͑or O − anion͒ from the relaxed, hydroxyl-free structure. The energies have been determined using the Perdew-Wang ͑PW91͒ implementation 31 of the exchange-correlation functional, this functional belongs to the family of methods developed under the so-called generalized gradient approximation ͑GGA͒.…”
Section: A Periodic Calculationsmentioning
confidence: 99%
“…, and a specific surface area below 10 m 2 g À1 [6]. Both characteristics limit the total amount of surface OH groups [7][8][9].…”
Section: à2mentioning
confidence: 99%